Citotoxicidade, genotoxicidade e monitoramento do ciclo celular e da indução de apoptose, dos alcaloides sanguinarina e cheleritrina, em linhagens celulares tumoral (HepG2/C3A e MCF-7) e não tumoral (MRC-5) humanas - Almeida, Igor Vivian de (2015)
The growing recurrence of tumors in human beings and severe side effects of chemotherapeutic agents reduce the clinical efficacy of a wide variety of anticarcinogenic substances routinely used. Therefore, there is always a constant need to develop and/or find alternative drugs for the treatment of cancer. Chemotherapeutic agents coming from plants and derivatives have proven effective in the treatment and prevention of this disease. Quaternary alkaloids benzo[c]phenanthridine, sanguinarine (SAN) and chelerythrine (CHE) can be found in different plants of the Papaveraceae family (Sanguinaria canadensis, Chelidonium majus, Macleaya cordata), among others, and have biological properties of interest, as activity, cytotoxic, genotoxic, antiproliferative and apoptotic. Thus, this study aimed to identify the cytotoxic, genotoxic, on the progression of the cell cycle and apoptotic of alkaloids SAN and CHE in different human cell lines. It was observed that SAN is cytotoxic to tumor cells of human hepatoma (HepG2/C3A) and non-tumor human lung fibroblast (MRC-5), effectively reducing cell viability at different times and concentrations. Analysis of membrane integrity showed that the tumor cell line is more resistant to the cytotoxic action of the alkaloid. The comet assay analysis indicated that the SAN is more genotoxic for the tumor cell line, whereas only the highest concentrations have the same effect on the non-tumor cell line. The cell cycle analysis indicated a population of non-tumor lineage cells in sub-G1, was confirmed by the apoptosis assay, due to the reduction in the percentage of viable cells and increased apoptosis or necrosis. The CHE alkaloid is cytotoxic to HepG2/C3A and MRC-5, reducing dose-dependent cell viability at different times and concentrations. Analysis of membrane integrity showed that CHE presents cytotoxic activity for both cell lines. The comet assay analysis indicated that the CHE, is more genotoxic for non-tumor cell line, while only higher concentrations have the same effect on the tumor cell line. The cell cycle analysis did not identify statistically significant differences in the progression of cell division in both strains. However, the apoptosis assay showed that the highest concentrations tested reduced the percentage of viable cells and increased the initial apoptosis, in both strains. The effects of alkaloids SAN and CHE were also evaluated in breast adenocarcinoma cells (MCF-7). It was observed that the SAN is cytotoxic to MCF-7 cells, effectively reducing cell viability at different times and concentrations, while CHE was cytotoxic, but not effectively reduced cell viability. The analysis of plasmatic membrane integrity showed that both alkaloids did not affect the cell viability and the analysis of comet assay indicated that the SAN was genotoxic to cells, whereas none of the evaluated concentrations of alkaloid CHE was genotoxic. The cell cycle analysis of MCF-7 treated with SAN showed no delays, but indicated a greater population of sub-G1 as a result of apoptotic or necrotic cells, whereas CHE caused no delay in the cell cycle and did not induce an increase of cells in sub-G1. Thus, the results of cytotoxicity, genotoxicity, cell cycle analysis and apoptosis induction presented in this study suggest that possibly the alkaloids, SAN and CHE can be employed in the development of new therapies related to cancer treatment..